Libraries versus the needs of people with neurodegenerative diseases - Malesa, Renata (Видавництво Львівської політехніки, 2025)
In the last few years, there has been a significant increase in the number of people suffering from neurodegenerative diseases, such as dementia and Alzheimer's disease, in Poland, Europe, and around the world. According to the World Health Organization (WHO), dementia is not only the leading cause of disability and need for care, but also the seventh leading cause of death. Therefore, many institutions are taking initiatives to prevent and ensure the improvement of the social functioning of people suffering from this disease, as well as their families. Libraries are playing an increasingly important role among these institutions. This paper discusses the activities of both Polish and global libraries and library organizations implementing projects regarding this area. Both guidelines for libraries as well as examples of good practices are presented in this paper.
Keywords: public libraries; dementia; neurodegenerative diseases; seniors; library associations